Needlestick injuries: the role of safety-engineered devices in prevention. (23rd July 2020) - Jackson, Andrew Paul; Almerol, Leo Andrew; Campbell, Jackie; Hamilton, Louise
Abstract : The first documented mention of a needlestick injury (NSI) in the medical literature appeared in 1906. Despite growth in academic and clinical interest for NSI prevention, a global report identified that approximately 3 million healthcare workers have suffered percutaneous exposure to blood-borne pathogens. Legislation is an important component of NSI prevention. Unfortunately, the impact of legislation may not always reduce the incidence of NSI as much as expected. Safety-engineered device (SED) implementation has demonstrated a substantial reduction in NSI rates compared with non-SEDs. More importantly, passive SEDs are 10 times less likely to be connected with an NSI incident